A column of fire - Follett, Ken (Viking, 2017)
"International bestselling author Ken Follett has enthralled millions of readers with The Pillars of the Earth and World Without End, two stories of the Middle Ages set in the fictional city of Kingsbridge. The saga now continues with Follett's magnificent new epic, A Column of Fire. In 1558, the ancient stones of Kingsbridge Cathedral look down on a city torn apart by religious conflict. As power in England shifts precariously between Catholics and Protestants, royalty and commoners clash, testing friendship, loyalty, and love. Ned Willard wants nothing more than to marry Margery Fitzgerald. But when the lovers find themselves on opposing sides of the religious conflict dividing the country, Ned goes to work for Princess Elizabeth. When she becomes queen, all Europe turns against England. The shrewd, determined young monarch sets up the country's first secret service to give her early warning of assassination plots, rebellions, and invasion plans. Over a turbulent half century, the love between Ned and Margery seems doomed as extremism sparks violence from Edinburgh to Geneva. Elizabeth clings to her throne and her principles, protected by a small, dedicated group of resourceful spies and courageous secret agents"--